Transitivity System in Hotel Slogans: Systemic Functional Linguistics Study - Salwa Fadila Firdaus; Sutiono Mahdi (Hasanuddin University, 2020)
AbstractThree metafunctions of meaning in Systemic Functional Linguistics are interpersonal meaning, textual meaning, and ideational meaning. In ideational meaning, it is realized through the transitivity system (Halliday, 2004). As for this study, it focuses on the analysis of processes type classification and what type of process that dominant in Bandung hotel slogans based on Halliday’s theory about transitivity. To present the findings, a qualitative descriptive study is applied as the research design. The documentation method is used to collect 36 Bandung hotel slogans. It appears that the relational process is the most dominant in the hotel slogan clauses in order to represent their brand to affect the customer’s mind.